COMMUNICATION ACROSS CULTURES AS CHARACTER EDUCATION IN THE LEARNING OF LANGUAGES AND LITERATURE IN INDONESIAN - Zulkifli Zulkifli (Proceedings Education and Language International Conference, 2017)
The diversity of culture is treasure the which is highly valued, but on the other hand, The differences that will not managed can give rise to various problems such as those often faced by this people. Communication cross culture could give variety in terms of culture and social organization in depth, Can learn about the development of individuals, family, gender, control over crime, and social inequalities. We can also said that the core idea of the communication of cross-cultural situated on a communication between people and different groups culture, Which are affected by the attitude, resources, and history and the process of interpretation and the interaction that influenced by participants in communication. Disparities economy, social, political, and inability people in understand the group has resulted in clashes. Education has been tending to give a serving that excessive aspects on planting competence hard skills and less member a serving that worthy on planting soft skills. Character education very influential to be able to cope with the human characters start from family , school , and environment communities through cross-cultural communication. Character of being characteristic of the one source of the environment. To improve the quality of learning in building character can through the habit of disciplined educator as well as learning atmosphere conducive using cross-cultural communication as education formation character. The learning of languages and literature Indonesian can develop human resource having intellectual and psychomotor about the rudiments speaking in relation to character education. In a system planting values character to the schools that includes components knowledge, consciousness or volition, and action to implement values through local culture.Keyword: the diversity, culture, education, communication, environment, learning